The effects of positive end-expiratory pressure on respiratory system mechanics and hemodynamics in postoperative cardiac surgery patients - Auler Jr.,J.O.C. (2000)
We prospectively evaluated the effects of positive end-expiratory pressure (PEEP) on the respiratory mechanical properties and hemodynamics of 10 postoperative adult cardiac patients undergoing mechanical ventilation while still anesthetized and paralyzed. The respiratory mechanics was evaluated by the inflation inspiratory occlusion method and hemodynamics by conventional methods. Each patient was randomized to a different level of PEEP (5, 10 and 15 cmH2O), while zero end-expiratory pressure (ZEEP) was established as control. PEEP of 15-min duration was applied at 20-min intervals. The frequency dependence of resistance and the viscoelastic properties and elastance of the respiratory system were evaluated together with hemodynamic and respiratory indexes. We observed a significant decrease in total airway resistance (13.12 ± 0.79 cmH2O l-1 s-1 at ZEEP, 11.94 ± 0.55 cmH2O l-1 s-1 (P<0.0197) at 5 cmH2O of PEEP, 11.42 ± 0.71 cmH2O l-1 s-1 (P<0.0255) at 10 cmH2O of PEEP, and 10.32 ± 0.57 cmH2O l-1 s-1 (P<0.0002) at 15 cmH2O of PEEP). The elastance (Ers; cmH2O/l) was not significantly modified by PEEP from zero (23.49 ± 1.21) to 5 cmH2O (21.89 ± 0.70). However, a significant decrease (P<0.0003) at 10 cmH2O PEEP (18.86 ± 1.13), as well as (P<0.0001) at 15 cmH2O (18.41 ± 0.82) was observed after PEEP application. Volume dependence of viscoelastic properties showed a slight but not significant tendency to increase with PEEP. The significant decreases in cardiac index (l min-1 m-2) due to PEEP increments (3.90 ± 0.22 at ZEEP, 3.43 ± 0.17 (P<0.0260) at 5 cmH2O of PEEP, 3.31 ± 0.22 (P<0.0260) at 10 cmH2O of PEEP, and 3.10 ± 0.22 (P<0.0113) at 15 cmH2O of PEEP) were compensated for by an increase in arterial oxygen content owing to shunt fraction reduction (%) from 22.26 ± 2.28 at ZEEP to 11.66 ± 1.24 at PEEP of 15 cmH2O (P<0.0007). We conclude that increments in PEEP resulted in a reduction of both airway resistance and respiratory elastance. These results could reflect improvement in respiratory mechanics. However, due to possible hemodynamic instability, PEEP should be carefully applied to postoperative cardiac patients.